Mid-gastric peroral endoscopic myotomy in the treatment of post-sleeve gastrectomy gastric tube twist: Four cases - Mugnier, Angelique; Vitton, Veronique; Barthet, Marc; Gonzalez, Jean-Michel (Endoscopy International Open, 2024)
Background and study aims Laparoscopic sleeve gastrectomy (LSG) may lead to symptomatic mid-gastric twist in 0.1% to 4% of cases. Endoscopic balloon dilatation often fails, requiring a switch to Roux-en-Y bypass. Submucosal endoscopic treatment is expanding, so we propose a new technique of fibrosis incision after tunnelization, called medio-gastric peroral endoscopic myotomy (MG-POEM).Patients and methods Four patients aged 41 to 70 years underwent MG-POEM in 2020 for symptomatic post-LSG medio-gastric twist. The aim was to describe the technique, and document the efficacy, using the Gastric Outlet Obstruction Scoring System (GOOSS) score and a quality-of-life scale (QOLS). The procedures consisted of a POEM with myotomy and fibrosis incision.Results Median preoperative GOOSS and QOLS were 1/3 ([0–3] and 1.75/10 [0–10], respectively. All procedures were technically successful. One patient had immediate postoperative complications, which were treated conservatively. The median follow-up was 18 months. All patients had improved quality of life and food intake, with median postoperative GOOSS and QOLS of 3/3 and 6,5/10 [6–8], respectively. Two patients required additional pneumatic dilatation for scarring strictures. Follow-up endoscopies and esophagograms showed that the twist had disappeared.Conclusions MG-POEM shows promise for safe and effective management of post-LSG mid-gastric twist, despite requiring a high level of endoscopic skill to perform submucosal tunneling.
Keywords: POEM; GI surgery; Benign strictures